DEVELOPMENTOF GEOGRAPHIC INFORMATION SYSTEMS BASED FACILITY MANAGEMENT OF AREA F STAFF HOUSING UNIT, AHMADU BELLO UNIVERSITY ZARIA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The research critically observed the process and methods involved in developing a GIDFM in A.B.U Zaria. In order to achieve the aim and objective of this research, Satellite images, Area F base map, coordinates and control points of the houses, attribute data of the houses such as a general information of the house, record of the surrounding environment, maintenance information about the houses all of which were collected through distribution of questionnaires to the occupants of the houses and visual inspection by the researcher and used to obtained the final results for the study. Multiple approaches of both ArcGIS 10.3 and questionnaires were employed. It was found that, there were 160 housing units in Area F. The study also shows that, one third of the infrastructure and facility of the housing units were in bad conditions and not properly managed. The study hereby recommends that there is the need for proper management of the infrastructure and facility in the housing units in order to enhance optimal performance of occupants at their various workplaces. Thus, GIS is an important tool in facility management.
Keywords: Facility, Management, Housing, Development and GIS.